Preparation method of composite phase change heat storage material of inorganic hydrated salt and metal organic framework

By combining inorganic hydrated salts with high-performance metal-organic frames (MOFs), the problems of supercooling and phase separation of inorganic hydrated salt phase change heat storage materials are solved, the heat storage performance and stability are improved, and the scope of application is expanded.

CN119775973APending Publication Date: 2025-04-08BEIJING ZHONGLI XINDA ENVIRONMENTAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411994491.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing inorganic hydrated salt phase change heat storage materials have problems with supercooling and phase separation, which limits their application scope in actual applications. In addition, the traditional porous material has a single structure and a pore structure that is not easy to adjust, resulting in insufficient heat storage performance.

Method used

Inorganic hydrated salts are combined with metal organic frames (MOFs) with high stability, high specific surface area and high porosity. Compound phase change heat storage materials are prepared by melt blending method, and the porous structure of MOFs and high specific surface area are used to improve the heat storage performance of inorganic hydrated salts.

Benefits of technology

By introducing MOFs, the heat storage performance of inorganic hydrated salt phase change materials is improved, its stability and energy storage performance are enhanced, and its application range is widened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775973A_ABST
    Figure CN119775973A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite phase change heat storage material of inorganic hydrated salt and a metal organic framework, and belongs to the technical field of phase change heat storage materials. The material is a low-temperature heat storage composite material prepared by combining an inorganic hydrated salt phase change material and a porous material. MOFs with high stability, high specific surface area and high porosity are selected to prepare a composite phase change heat storage material as a porous carrier, the porous carrier and traditional inorganic hydrated salt are used for preparing the composite phase change material, and the heat storage performance of the composite material is researched. According to the composite phase change heat storage material prepared by the preparation method of the composite phase change heat storage material of the inorganic hydrated salt and the metal organic framework, the melting point of the composite phase change heat storage material with the addition proportion of 2.4 wt.% is the highest; the latent heat of the composite phase change heat storage material with the addition proportion of 2.4 wt.% is lower than that of Na2SO4. 10H2O.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of phase change heat storage materials, and specifically relates to a method for preparing a composite phase change heat storage material of an inorganic hydrated salt and a metal organic framework. Background Art

[0002] Energy is the basis of human life and production. With the rapid development of the economy, energy shortages are becoming increasingly obvious, and the human living environment is facing a huge crisis. Therefore, the development of renewable energy and the improvement of energy utilization efficiency have received increasing attention from researchers. As a highly efficient energy storage material, phase change thermal storage materials (PCMs) use the endothermic and exothermic effects of materials during phase change to store and release energy. They have many advantages such as high energy storage density, wide range of phase change temperature selection, and stable performance, and are widely used (Chem. Rev. 2023, 123, 6953).

[0003] As a typical inorganic phase change energy storage material, inorganic hydrated salts have the characteristics of being cheap and easy to obtain, stable chemical properties, high heat storage density and high thermal conductivity. However, this type of material has problems such as supercooling and phase separation. For example, when used above the melting temperature, the leakage of solid-liquid PCMs in the liquid phase will limit its direct application. These problems have restricted its application in actual production to a certain extent (Renew.Sust.Energ.Rev.2017,70,1072). Compared with traditional single phase change materials, selecting ideal porous materials to construct composite phase change energy storage materials can optimize the energy storage value of the composite material by changing the percentage of porous materials, and with the help of the inherent capillary force, surface tension and hydrogen bond of porous materials, the stability of single phase change energy storage materials can be improved through composite, the energy storage performance of single phase change energy storage materials can be enhanced, the defects of single phase change energy storage materials can be improved, and the application range of phase change energy storage materials can be expanded (Energy Environ.Sci.2020,13,4498;2023,16,830). Commonly used porous materials include metal foam, expanded graphite, and graphene. However, these materials have a single structure, difficult to adjust the pore structure, and a small specific surface area. Therefore, it is necessary to explore new porous materials to prepare high-performance composite phase change energy storage materials.

[0004] Metal-Organic Frameworks (MOFs) materials are highly ordered porous organic-inorganic hybrid materials formed by coordination between metal ions and organic ligands. They have the characteristics of high specific surface area, high porosity, diverse and adjustable structure, and stable chemical properties (Chem.Soc.Rev.2023,52,6918). They are currently widely used in many fields such as gas storage, adsorption separation, and catalysis (Coord.Chem.Rev.2020,422,213470; 2022,470,214707; Chem.Soc.Rev.2022,51,7138; 2023,52,7549; Chem.Rev.2023,123,6545). In recent years, MOFs have become an emerging carrier for the preparation of composite phase change energy storage materials, and the research on MOFs-based composite phase change energy storage materials has attracted much attention (Energy Storage Mater. 2019, 18, 349; Energy Environ. Sci. 2020, 13, 4498).

[0005] Currently, commonly used porous materials include metal foam, expanded graphite, and graphene, etc. In the prior art, most of the thermal storage composite materials are made by combining organic materials with porous materials. However, these materials have a single structure, the pore structure is not easy to adjust, and the specific surface area is small. Summary of the invention

[0006] In view of the shortcomings of the heat storage performance of inorganic phase change heat storage materials, the first purpose of the present invention is to provide a method for preparing a composite phase change heat storage material of an inorganic hydrated salt and a metal organic framework, taking a low-temperature phase change heat storage material such as Na2SO4·10H2O as the research object, selecting MOFs with high stability, high specific surface area, and high porosity such as MILs, ZIFs, and UiO series to prepare composite phase change heat storage materials as porous carriers, and preparing composite phase change materials with traditional inorganic hydrated salts to study the heat storage performance of composite materials. The inorganic hydrated salt phase change material is modified by the introduction of porous MOFs to improve the heat storage performance of traditional inorganic hydrated salt phase change materials.

[0007] The second purpose of the present invention is to provide a method for preparing a composite phase change heat storage material of an inorganic hydrated salt and a metal organic framework. In the present application, an inorganic hydrated salt phase change material is combined with a porous material to prepare a low-temperature heat storage composite material.

[0008] The present invention is achieved through the following technical solutions:

[0009] A method for preparing a composite phase change heat storage material of an inorganic hydrated salt and a metal organic framework, comprising selecting an inorganic phase change heat storage material and mixing it with a metal organic framework, and preparing the composite phase change heat storage material by a melt blending method;

[0010] The inorganic phase change heat storage material is Na2SO4·10H2O;

[0011] The metal organic framework is any one of MIL-101, ZIF-8 and UiO-66;

[0012] The mixing mass ratio of the inorganic phase change heat storage material to the metal organic framework is 1-4g:0.01-0.1g;

[0013] The composite phase-change heat storage material is calculated as 100%, and the mass fraction of the added metal organic framework is 2.4-4.8%.

[0014] Preferably, the metal organic framework is ZIF-8.

[0015] The inorganic phase change heat storage material Na2SO4·10H2O is composed of 55.91% water and 44.09% sodium sulfate inorganic salt. Its heat storage capacity per unit volume is more than 4 times that of water with a temperature difference of 20°C. It is a classic phase change heat storage / cold storage material and is often used in industrial waste heat utilization and solar heating.

[0016] Metal organic frameworks (MOFs), MOFs have a large specific surface area and can be used as an adsorption matrix. They can use their surface intrinsic tension and capillary adsorption to adsorb molten phase change heat storage materials into the pores of porous materials to form composite phase change heat storage materials; MOFs are designable, and by extending the length and rigidity of organic ligands, the packing density of phase change materials is enhanced, thereby increasing the heat storage capacity of phase change heat storage materials; the pore wall structure can be modified by introducing functional groups to further enhance the adsorption of phase change heat storage materials, so that the phase change process occurs in the pores or cavities, thereby enhancing its thermal stability.

[0017] Preferably, the preparation method of ZIF-8 is:

[0018] S1, select 2-methylimidazole and 99.5% methanol to mix to form solution A;

[0019] S2, select a metal zinc source and mix it with methanol with a mass concentration of 99.5% to form solution B;

[0020] S3. Mix solution A and solution B and stir for 10 to 12 hours to obtain a white milky precipitate. After centrifugation, washing and drying, ZIF-8 is obtained.

[0021] Preferably, the mixing mass ratio of the 2-methylimidazole to 99.5% methanol is 1:5.5;

[0022] The metal zinc source and methanol with a mass concentration of 99.5% are mixed in a mass ratio of 1:12;

[0023] The mixing mass ratio of solution A and solution B is 1.1:1.0.

[0024] Preferably, the centrifugal speed is 8000 rpm and the duration is 5 to 8 minutes.

[0025] Preferably, the washing is performed using ethanol with a mass concentration of 70-75%, and the number of washing times is 3-4 times;

[0026] The drying time is 10 to 12 hours, and the drying temperature is 50 to 60 degrees.

[0027] Preferably, the metallic zinc source is zinc nitrate.

[0028] Preferably, the inorganic phase change heat storage material is mixed with the metal organic framework to prepare the composite phase change heat storage material by melt blending method as follows:

[0029] S1. Weigh the inorganic phase change heat storage material using an electronic balance and place it in a beaker, ultrasonically heat it to a molten state, and set aside;

[0030] S2, adding the metal organic framework to the above-mentioned molten inorganic phase change thermal storage material, and promoting the metal organic framework to be uniformly dispersed in the molten salt of the inorganic phase change thermal storage material by ultrasonic treatment to obtain a mixed solution A;

[0031] S3. Naturally cool the mixed solution A to room temperature to obtain a composite phase change heat storage material.

[0032] Preferably, in S1, the temperature of ultrasonic heating is 50-80° C., and the ultrasonic heating time is 5-20 min.

[0033] Preferably, in S2, the ultrasonic treatment duration is 10 to 20 minutes.

[0034] Compared with the prior art, the present invention has at least the following technical effects:

[0035] (I) The present invention provides a method for preparing a composite phase change heat storage material of an inorganic hydrated salt and a metal organic framework, taking a low-temperature phase change heat storage material such as Na2SO4·10H2O as the research object, selecting MOFs with high stability, high specific surface area, and high porosity such as MILs, ZIFs, and UiO series to prepare a composite phase change heat storage material as a porous carrier, and preparing a composite phase change material with a traditional inorganic hydrated salt, and studying the heat storage performance of the composite material. The inorganic hydrated salt phase change material is modified by the introduction of porous MOFs, and the heat storage performance of the traditional inorganic hydrated salt phase change material is improved.

[0036] (ii) A method for preparing the composite phase change heat storage material of the inorganic hydrated salt and the metal organic framework. In the present application, the low-temperature heat storage composite material is prepared by combining the inorganic hydrated salt phase change material with a porous material.

[0037] (III) Through the basic characterization spectrum diffraction peaks and infrared spectrum absorption peaks of the composite phase change heat storage material, combined with the latent heat analysis and thermal stability analysis in the heat storage performance, it is known that the composite phase change heat storage material prepared by the preparation method of the composite phase change heat storage material of inorganic hydrated salt and metal organic framework has the highest melting point of the composite phase change heat storage material with an addition ratio of 2.4wt.%; the composite phase change heat storage material with an addition ratio of 2.4wt.% has a lower latent heat than Na2SO4·10H2O. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The preparation process of Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material;

[0039] Figure 2 PXRD patterns of ZIF-8, Na2SO4·10H2O and Na2SO4·10H2O@ZIF-8;

[0040] Figure 3 Infrared spectra of ZIF-8, Na2SO4·10H2O and Na2SO4·10H2O@ZIF-8. DETAILED DESCRIPTION

[0041] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0042] Terminology explanation:

[0043] Phase Change Materials (PCMs)

[0044] Metal-Organic Frameworks (MOFs).

[0045] Among them, MOFs materials include zeolitic imidazolate framework materials (ZIFs), Materials of institute lavoisier (MILs) and University of Oslo series (UiO).

[0046] A technical solution of a specific implementation of the present invention is:

[0047] A method for preparing a composite phase change heat storage material of an inorganic hydrated salt and a metal organic framework comprises the following steps:

[0048] 1. Select the traditional inorganic phase change heat storage material Na2SO4·10H2O as the phase change heat storage material, add different MOFs such as MIL-101, ZIF-8, and UiO-66, and prepare Na2SO4·10H2O@MOFs composite phase change material by melt blending method.

[0049] 2. Characterize the composite phase change heat storage material by PXRD, FT-IR, etc.; use differential scanning calorimetry (DSC) to test the effect of adding different MOFs on the melting point, phase change latent heat and other heat storage properties of Na2SO4·10H2O; select the best MOFs as adsorbents to obtain the optimal Na2SO4·10H2O@MOFs composite phase change material.

[0050] 3. Na2SO4·10H2O@MOFs composite phase change thermal storage material was prepared by melt blending method, in which MOFs was described in detail by taking ZIF-8 as an example:

[0051] a) Preparation of ZIF-8: 2-methylimidazole and methanol are prepared into solution A, and a metal zinc source (zinc nitrate) is used as a solute and methanol is used as a solvent to prepare solution B; solution A and solution B are mixed and stirred for 10 to 12 hours to obtain a white milky precipitate, which is centrifuged, washed with ethanol, and dried to obtain ZIF-8.

[0052] b) Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material

[0053] A certain mass of Na2SO4·10H2O is weighed with an electronic balance and placed in a beaker, and ultrasonically heated to a molten state; different masses of ZIF-8 are added to the molten Na2SO4·10H2O, and ultrasound can be used to assist the uniform dispersion of ZIF-8 in the Na2SO4·10H2O molten salt; the mixed sample is naturally cooled to room temperature to obtain a Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material.

[0054] c) Basic characterization of composite phase change thermal storage materials:

[0055] The XRD spectrum marked the diffraction peaks of the materials Na2SO4·10H2O and ZIF-8, and the crystal plane distance basically did not change, indicating that Na2SO4·10H2O and ZIF-8 were successfully compounded and no chemical reaction occurred.

[0056] The infrared spectrum characterizes the absorption peak positions of Na2SO4·10H2O and ZIF-8. The analysis shows that no new groups are generated in the composite phase change thermal storage material, which further indicates that the material is successfully composited and no chemical reaction occurs.

[0057] d) Heat storage performance test:

[0058] Latent heat analysis: DSC test was carried out on the composite phase change heat storage material, and the melting point of the composite materials with different ZIF-8 addition ratios was compared with the single component Na2SO4·10H2O to prove how the addition of ZIF-8 positively affects the phase change temperature of Na2SO4·10H2O, indicating that the composite material has high latent heat and good heat storage performance.

[0059] Thermal stability analysis: Thermogravimetric analysis is used to evaluate the thermal stability of phase change thermal storage materials. The higher the decomposition temperature of the phase change thermal storage material, the better its thermal stability. The reduction of mass loss can reduce the operating cost of the thermal energy storage system and greatly improve the heat transfer performance and thermal stability of the material.

[0060] Embodiment 1:

[0061] A preparation method of a composite phase change heat storage material of an inorganic hydrated salt and a metal organic framework, comprising the following steps: Na2SO4·10H2O@ZIF-8 composite phase change heat storage material synthesis method:

[0062] Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material was prepared by melt blending method and ultrasonic assisted.

[0063] like Figure 1 Shown is the preparation process of Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material.

[0064] The synthesis process is as follows:

[0065] a) Weigh 2 g of Na2SO4·10H2O using an electronic balance, place it in an ultrasonic cleaning machine heated to 80°C in advance, control the ultrasonic time to 20 minutes, and wait until the Na2SO4·10H2O sample is heated to a molten state;

[0066] b) adding ZIF-8 powder (mass 0.000 g) into Na2SO4·10H2O No. 1, and ultrasonicating for 20 min according to the predetermined time;

[0067] c) The mixed sample is naturally cooled to room temperature to obtain Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material. The sample number is shown in Sample 1 in Table 1.

[0068] Embodiment 2:

[0069] A preparation method of a composite phase change heat storage material of an inorganic hydrated salt and a metal organic framework, comprising the following steps: Na2SO4·10H2O@ZIF-8 composite phase change heat storage material synthesis method:

[0070] Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material was prepared by melt blending method and ultrasonic assisted.

[0071] like Figure 1 Shown is the preparation process of Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material.

[0072] The synthesis process is as follows:

[0073] a) Weigh 2 g of Na2SO4·10H2O using an electronic balance, place it in an ultrasonic cleaning machine heated to 80°C in advance, control the ultrasonic time to 20 minutes, and wait until the Na2SO4·10H2O sample is heated to a molten state;

[0074] b) adding ZIF-8 powder (mass 0.050 g) into Na2SO4·10H2O in No. 2, and ultrasonicating for 20 min according to the predetermined time;

[0075] c) The mixed sample is naturally cooled to room temperature to obtain Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material. The sample number is shown in Sample 2 in Table 1.

[0076] Embodiment 3:

[0077] A preparation method of a composite phase change heat storage material of an inorganic hydrated salt and a metal organic framework, comprising the following steps: Na2SO4·10H2O@ZIF-8 composite phase change heat storage material synthesis method:

[0078] Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material was prepared by melt blending method and ultrasonic assisted.

[0079] like Figure 1 Shown is the preparation process of Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material.

[0080] The synthesis process is as follows:

[0081] a) Weigh 2 g of Na2SO4·10H2O using an electronic balance, place it in an ultrasonic cleaning machine heated to 80°C in advance, control the ultrasonic time to 20 minutes, and wait until the Na2SO4·10H2O sample is heated to a molten state;

[0082] b) adding ZIF-8 powder (mass 0.075 g) into Na2SO4·10H2O in No. 3, and ultrasonicating for 20 min according to the predetermined time;

[0083] c) The mixed sample is naturally cooled to room temperature to obtain Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material. The sample number is shown in Sample 3 in Table 1.

[0084] Embodiment 4:

[0085] A preparation method of a composite phase change heat storage material of an inorganic hydrated salt and a metal organic framework, comprising the following steps: Na2SO4·10H2O@ZIF-8 composite phase change heat storage material synthesis method:

[0086] Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material was prepared by melt blending method and ultrasonic assisted.

[0087] like Figure 1 Shown is the preparation process of Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material.

[0088] The synthesis process is as follows:

[0089] a) Weigh 2 g of Na2SO4·10H2O using an electronic balance, place it in an ultrasonic cleaning machine heated to 80°C in advance, control the ultrasonic time to 20 minutes, and wait until the Na2SO4·10H2O sample is heated to a molten state;

[0090] b) adding ZIF-8 powder (mass 0.100 g) into Na2SO4·10H2O in No. 4, and ultrasonicating for 20 min according to the predetermined time;

[0091] c) The mixed sample is naturally cooled to room temperature to obtain Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material. The sample number is shown in Sample 4 in Table 1.

[0092] Embodiment 5:

[0093] A preparation method of a composite phase change heat storage material of an inorganic hydrated salt and a metal organic framework, comprising the following steps: Na2SO4·10H2O@ZIF-8 composite phase change heat storage material synthesis method:

[0094] Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material was prepared by melt blending method and ultrasonic assisted.

[0095] like Figure 1 Shown is the preparation process of Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material.

[0096] The synthesis process is as follows:

[0097] a) Weigh 1.50 g of Na2SO4·10H2O using an electronic balance, place it in an ultrasonic cleaning machine preheated to 50°C, control the ultrasonic time to 5 minutes, and wait until the Na2SO4·10H2O sample is heated to a molten state;

[0098] b) adding ZIF-8 powder (mass 0.010 g) into Na2SO4·10H2O and sonicating for 10 min according to the predetermined time;

[0099] c) The mixed sample was naturally cooled to room temperature to obtain Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material.

[0100] Embodiment 6:

[0101] A preparation method of a composite phase change heat storage material of an inorganic hydrated salt and a metal organic framework, comprising the following steps: Na2SO4·10H2O@ZIF-8 composite phase change heat storage material synthesis method:

[0102] Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material was prepared by melt blending method and ultrasonic assisted.

[0103] like Figure 1 Shown is the preparation process of Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material.

[0104] The synthesis process is as follows:

[0105] a) Weigh 3.00 g of Na2SO4·10H2O using an electronic balance, place it in an ultrasonic cleaning machine heated to 50°C in advance, control the ultrasonic time to 10 minutes, and wait until the Na2SO4·10H2O sample is heated to a molten state;

[0106] b) adding ZIF-8 powder (mass 0.100 g) into Na2SO4·10H2O and ultrasonicating for 15 min according to the predetermined time;

[0107] c) The mixed sample was naturally cooled to room temperature to obtain Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material.

[0108] 1. Experimental samples:

[0109] Table 1 Sample number and addition ratio

[0110]

[0111] 2. Experimental test results and analysis

[0112] 2.1 X-ray powder diffraction analysis

[0113] like Figure 2 Shown are the PXRD patterns of ZIF-8, Na2SO4·10H2O and Na2SO4·10H2O@ZIF-8.

[0114] In the figure, ZIF-8 has multiple strong diffraction peaks at low angles of 2θ=7.4°, 10.5°, 12.8°, 14.7° and 18.1° ( Figure 2 mark).

[0115] Na2SO4·10H2O has strong diffraction peaks at 2θ=16.5°, 28.5°, 29.5°, 49.2° and 60.0° ( Figure 2 mark).

[0116] like Figure 2 The results show that in the XRD spectrum of the Na2SO4·10H2O@ZIF-8 composite phase change heat storage material, characteristic peaks appeared at the same position of the diffraction peaks of the single material ZIF-8 and Na2SO4·10H2O, and no new peaks appeared, indicating that no chemical reaction occurred between the two in the process of preparing the composite phase change heat storage material, but only physical mixing.

[0117] 2.2 Fourier transform infrared spectroscopy analysis

[0118] like Figure 3Shown are the infrared spectra of ZIF-8, Na2SO4·10H2O and Na2SO4·10H2O@ZIF-8.

[0119] from Figure 3 It can be seen that ZIF-8 has a peak at 1420 cm -1 、1310cm -1 、750cm -1 and 610cm -1 There is a strong characteristic absorption peak at 1075cm -1 There is a broad characteristic absorption peak at 615cm -1 There is a strong characteristic absorption peak.

[0120] In the spectrum of Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material, the -1 、1310cm -1 and 758cm -1 The absorption peak at 1100 cm-1 corresponds to the characteristic absorption peak of ZIF-8. -1 The broad absorption peak at 610 cm-1 is attributed to the characteristic absorption peak of Na2SO4·10H2O. -1 The strong absorption peak is attributed to the superposition of the characteristic absorption peak of ZIF-8 and the characteristic absorption peak of Na2SO4·10H2O.

[0121] The characteristic absorption peaks of Na2SO4·10H2O and ZIF-8 appeared simultaneously in the infrared spectrum of Na2SO4·10H2O@ZIF-8.

[0122] The analysis of functional groups shows that no new groups are generated in the Na2SO4·10H2O@ZIF-8 composite phase change thermal storage material.

[0123] No new substances are generated in the composite of Na2SO4·10H2O and ZIF-8, that is, there is no chemical reaction between Na2SO4·10H2O and ZIF-8, only physical mixing, which is consistent with the PXRD spectrum results.

[0124] 2.3 Melting point latent heat analysis

[0125] DSC tests were carried out on Na2SO4·10H2O and Na2SO4·10H2O@ZIF-8 composite phase change heat storage materials (protective gas N2, with an inflow rate of 20 mL·min-1; heating rate of 5℃·min-1; test temperature range of 20-70℃).

[0126] The results in Table 2 show that the melting temperature of Na2SO4·10H2O is 31.8℃, while the melting points of Na2SO4·10H2O@ZIF-8 composite phase change thermal storage materials are higher than that of Na2SO4·10H2O.

[0127] The melting point of the composite phase change thermal storage material with an addition ratio of 2.4wt.% is the highest, 8.8% higher than that of Na2SO4·10H2O, indicating that the addition of ZIF-8 will increase the melting point of Na2SO4·10H2O.

[0128] In the DSC test at a temperature range of 20 to 70 °C, the latent heat of fusion of Na2SO4·10H2O is 231.7 J·g -1 , adding different proportions of ZIF-8 has different effects on the phase change latent heat of Na2SO4·10H2O.

[0129] The latent heat of the composite phase change heat storage materials with addition ratios of 3.6wt.% and 4.8wt.% is higher than that of pure Na2SO4·10H2O, which are 243.6J·g -1 and 238.7 J·g -1 , 5.1% and 3.0% higher respectively.

[0130] The latent heat of the composite phase change heat storage material with a ratio of 2.4wt.% is 223.8J·g -1 , which is 3.4% lower than that of Na2SO4·10H2O.

[0131] Table 2 Melting point and phase change latent heat of Na2SO4·10H2O and Na2SO4·10H2O@ZIF-8 composite phase change thermal storage materials

[0132] Addition ratio (wt.%) Melting point(℃) Latent heat of phase change (J·g-1) 0 31.8 231.7 2.4 34.6 223.8 3.6 33.7 243.6 4.8 33.4 238.7

[0133] in conclusion:

[0134] 1. The melting points of the composite phase change heat storage materials with addition ratios of 2.4wt.%, 3.6wt.% and 4.8wt.% are all higher than that of Na2SO4·10H2O, among which the melting point of the composite phase change heat storage material with addition ratio of 2.4wt.% is the highest;

[0135] 2. The latent heat of the composite phase change heat storage materials with an addition ratio of 3.6wt.% and 4.8wt.% is higher than that of pure Na2SO4·10H2O, while the latent heat of the composite phase change heat storage material with an addition ratio of 2.4wt.% is lower than that of Na2SO4·10H2O.

[0136] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite phase change heat storage material of an inorganic hydrated salt and a metal organic framework, characterized in that: The method comprises selecting an inorganic phase change heat storage material and mixing it with a metal organic framework, and preparing a composite phase change heat storage material by a melt blending method; The inorganic phase change heat storage material is Na2SO4·10H2O; The metal organic framework is any one of MIL-101, ZIF-8 and UiO-66; The mixing mass ratio of the inorganic phase change heat storage material to the metal organic framework is 1-4g:0.01-0.1g; The composite phase-change heat storage material is calculated as 100%, and the mass fraction of the added metal organic framework is 2.4-4.8%.

2. The method for preparing a composite phase change thermal storage material of an inorganic hydrated salt and a metal organic framework according to claim 1, characterized in that: The metal organic framework is ZIF-8.

3. The method for preparing a composite phase change thermal storage material of an inorganic hydrated salt and a metal organic framework according to claim 2, characterized in that: The preparation method of the ZIF-8 is: S1, select 2-methylimidazole and 99.5% methanol to mix to form solution A; S2, select a metal zinc source and mix it with methanol with a mass concentration of 99.5% to form solution B; S3. Mix solution A and solution B and stir for 10 to 12 hours to obtain a white milky precipitate. After centrifugation, washing and drying, ZIF-8 is obtained.

4. The method for preparing a composite phase change thermal storage material of an inorganic hydrated salt and a metal organic framework according to claim 3, characterized in that: The mixing mass ratio of the 2-methylimidazole to 99.5% methanol is 1:5.5; The metal zinc source and methanol with a mass concentration of 99.5% are mixed in a mass ratio of 1:12; The mixing mass ratio of solution A and solution B is 1.1:1.

0.

5. The method for preparing a composite phase change thermal storage material of an inorganic hydrated salt and a metal organic framework according to claim 4, characterized in that: The centrifugal speed is 8000 rpm and the duration is 5 to 8 minutes.

6. The method for preparing a composite phase change thermal storage material of an inorganic hydrated salt and a metal organic framework according to claim 4, characterized in that: The washing is performed using ethanol with a mass concentration of 70-75%, and the number of washing times is 3-4 times; The drying time is 10 to 12 hours, and the drying temperature is 50 to 60 degrees.

7. The method for preparing a composite phase change thermal storage material of an inorganic hydrated salt and a metal organic framework according to claim 4, characterized in that: The metallic zinc source is zinc nitrate.

8. The method for preparing a composite phase change thermal storage material of an inorganic hydrated salt and a metal organic framework according to claim 1, characterized in that: The specific process of selecting an inorganic phase change heat storage material and mixing it with a metal organic framework to prepare a composite phase change heat storage material by melt blending is as follows: S1. Weigh the inorganic phase change heat storage material using an electronic balance and place it in a beaker, ultrasonically heat it to a molten state, and set aside; S2, adding the metal organic framework to the above-mentioned molten inorganic phase change thermal storage material, and promoting the metal organic framework to be uniformly dispersed in the molten salt of the inorganic phase change thermal storage material by ultrasonic treatment to obtain a mixed solution A; S3. Naturally cool the mixed solution A to room temperature to obtain a composite phase change heat storage material.

9. The method for preparing a composite phase change thermal storage material of an inorganic hydrated salt and a metal organic framework according to claim 8, characterized in that: In S1, the temperature of ultrasonic heating is 50-80° C., and the ultrasonic heating time is 5-20 min.

10. The method for preparing a composite phase change thermal storage material of an inorganic hydrated salt and a metal organic framework according to claim 8, characterized in that: In S2, the ultrasonic treatment time is 10 to 20 minutes.

Citation Information

Patent Citations

  • Preparation method of metal organic framework based composite phase-change material

    CN103756646A

  • Method for preparing multilevel porous carbon base composite phase change material

    CN104710965A

  • Phase change energy storage material based on MOFs and preparation method thereof

    CN108997974A

  • Method for generating fixed form of hydrous salt phase-change material and adjusting phase-change temperature by adding inorganic porous material

    CN109810675A